PEDAGOGICAL INTERACTION IN THE «TEACHER-STUDENT» DIAD IN ONLINE LEARNING CONDITIONS - Shvedova, Yaroslava (Educological discourse, 2021)
The article presents the results of a questionnaire survey of modern students regarding their educational needs and expectations in the context of forced online learning caused by the COVID-19 pandemic. The generalization of the educational needs and expectations of modern students, as well as the tendencies characteristic of them in teaching, made it possible to identify a range of problematic accents, which relate to: coordination and management on the part of teachers of the process of mastering the educational material by students; factors that enhance learning motivation, as well as factors that demotivate; the needs of modern students for the presentation of educational content; attitude to forms and methods of teaching in the context of modern changes; features of transformation of communication between students and teachers; feedback, etc. The study revealed some features of the interaction of modern students with the educational environment, their learning needs and expectations: openness to new forms and methods of teaching, the desire to express and manifest their position, the desire for interaction and exchange of views, the desire to be heard about the expected format or presentation of educational information, the desire to do what is interesting and have space for the implementation of their own educational path. Modern students expect from the teacher an interactive presentation of lecture material that has a problematic and exploratory nature. Based on the results of the survey, as well as on current trends characteristic of higher education in the context of transformational changes and forced distance learning caused by the COVID-19 pandemic, the ways of optimal pedagogical interaction in the teacher-student dyad are outlined.